Effectiveness of PhET Simulation Creative Problem-Solving Learning Model On Students' Problem-Solving Abilities - Bintang Maharani; Indri Hertika; Alifah Miftahul Jannah (Yayasan Siti Widhatul Faeha Salahudin Syawal, 2025)
The development of educational technology encourages the use of innovative methods in learning. Therefore, this study aims to measure the effectiveness of the Creative Problem Solving (CPS) learning model, assisted by PhET Simulation, on students' problem-solving abilities. The purpose of this study was to determine how the application of the CPS model can improve students' problem-solving abilities. The method employed was a quasi-experimental design with a Nonequivalent Control Group Design, involving two groups: an experimental class that implemented CPS with PhET and a control class that followed conventional learning methods. The data analysis technique involved comparing the initial and final test scores of the two groups. The results showed that the experimental class experienced a significant increase in problem-solving abilities, with a final average score of 79.55, whereas the control class achieved a score of 71.83. This study concludes that the CPS model, when supplemented by PhET, is capable of enhancing students' critical thinking skills and creativity, while also fostering a more engaging learning process. Suggestions for further research include exploring the use of technology in education to enhance the effectiveness of learning across various disciplines.